Quantitative proteomic analysis of chromatin-bound proteins in the fission yeast Schizosaccharomyces pombe - Wang, Han (2012)
Non-histone chromatin-associated proteins (CAPs) play important roles in regulating various biological processes requiring physical interaction with the chromatin. Chromatin fractionation assay fails to effectively deplete the highly abundant non-CAPs such as ribosomal proteins, hampering the de novo identification of Non-histone CAPs. In this study, we applied SILAC-mediated proteomic analysis to compare the relative abundance of proteins between chromatin extract and whole cell extract. We found that highly abundant ribosomal proteins were greatly depleted in the top SILAC-ranked proteins. Moreover, the potential non-histone CAPs were enriched in the top SILAC-ranked proteins. We also found the SILAC-enriched nucleus-localized proteins were more likely to play a role in growth fitness under DNA damage stress than the SILAC-depleted ones. Two novel top SILAC-ranked proteins were found to be true non-histone CAPs and selected for functional analysis. Therefore, SILAC-mediated proteomic approach is capable of determining non-histone CAPs without prior knowledge.